P-197 Postoperative Outcomes in Vedolizumab-Treated Pediatric Patients Undergoing Abdominal Operations for Crohn's Disease. (February 2017) - Lightner, Amy; Chang, Melissa; Mathis, Kellie; Pemberton, John; Faubion, William
Abstract : Background: Vedolizumab was recently FDA approved for treatment of moderate to severe ulcerative colitis (UC) and Crohn's disease (CD). A recent study found vedolizumab to be an independent predictor of increased rates of postoperative complications and surgical site infections (SSIs) in the adult UC/CD population. No study to date has investigated the rate of postoperative infectious complications among pediatric patients who received vedolizumab in the perioperative period. We sought to determine the 30-day postoperative infectious complication rate among IBD patients who received vedolizumab within 12 weeks of an abdominal operation. Methods: A retrospective chart review between January 5, 2014 and January 6, 2016 of adult IBD patients who underwent an abdominal operation was performed. The study cohort was comprised of pediatric patients (<18 yr) who received vedolizumab within 12 weeks of their abdominal operation. Results: Five pediatric patients (3 female) with CD received vedolizumab within 12 weeks of an abdominal operation. The median age at the time of their operation was 15 years (range 14–17 yr), median length of disease duration was 7 years (range 3–12 yr), and all patients had previously received anti-TNF. Three patients had had prior abdominal operations related to their CD. At the time of their operation, the median hemoglobin was 10.7 g/dL (range 9.9–12.9 g/dL), mean platelet count was 440 × 103 (range 230–677 × 103), and median albumin was 3.9 g/dL (range 3.6–4.0 g/dL). The median time from most recent dose of vedolizumab to surgery was 22 days (range 11–50 d). The operations performed were diverting loop ileostomy (n = 2), left hemicolectomy with end ileostomy (n = 1), ileocolic resection (n = 1), and small bowel resection with end ileostomy (n = 1). No patient experienced 30-day mortality, 30 days superficial or deep space SSI, need for readmission or need for reoperation. Conclusions: None of the 5 pediatric patients who received vedolizumab within 12 weeks of an abdominal operation experienced a 30-day postoperative complication or SSI, suggesting that vedolizumab is safe in the perioperative period for pediatric patients with CD. Due to the small sample size, future study, perhaps multi-institutional, will be important to confirm these findings.